Expert System for Diagnosis of Hypertension Disease Using Naive Bayes Method - Edhy Poerwandono; Prakoso Angga Ilyasa (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
Hypertension is a disorder of the blood vessels that causes the supply of oxygen and nutrients carried by the blood to be blocked to the body's tissues that need it. Hypertension is often referred to as a silent killer, because it is a deadly disease without symptoms as a warning to its victims. Hypertension sufferers range from 40 years of age and above to lifelong. In general, hypertension is caused by hereditary factors, unhealthy lifestyles, excessive salt consumption, alcoholic beverages and stress. Expert systems can be a solution to solve problems because this system works like an expert and is designed using the naive bayes method by looking at the rules and rule bases that exist in hypertension. Through this application, users can consult with the system like consulting an expert to diagnose the symptoms that occur in users and find solutions to the problems faced.